Through the eyes of a child : an introduction to children's literature - Norton, Donna E. (Ohio : Merrill Publishing Company, 1987)
This text is intended for any adult who is interested in evaluating, selecting, and sharing children's literature.
1. The child and children's literature -- 2. History of children's literature -- 3. Evaluating and selecting literature for children -- 4. Artists and their illustrations -- 5. Picture books 140 -- 6. Traditional literature -- 7. Modern fantasy -- 8. Poetry -- 9. Contemporary realistic fiction -- 10. Historical fiction.
Includes index.
Keywords: CHILD DEVELOPMENT